The Role of Smoking Cessation in Cardiovascular Disease - AM Ambari (Faculty of Medicine, Public Health and Nursing Universitas Gadjah Mada, 2017)
Indonesia is in the world 1st rank for the number of male smokers over the age of 15 years. It......